The influence of the processing route on the fragmentation of (Nb, Ti)C stringers and its role on mechanical properties and hydrogen embrittlement of nickel based alloy 718. (26th April 2021) - Araujo, Leonardo Sales; Guimarães, Alessandra Vieira; Siqueira, Maísa Conceição; Mendes, Matheus Campolina; Mallet, Loic; Silva dos Santos, Dilson; Henrique de Almeida, Luiz
Abstract: The nickel-base superalloy 718 is a precipitation hardened alloy widely used in the nuclear fuel assembly of pressurized water reactors (PWR). However, the alloy can experience failure due to hydrogen embrittlement (HE). The processing route can influence the microstructure of the material and, therefore, the HE degree. In particular, the size and distribution of the (Nb, Ti)C particles can be affected by the processing. In this regard, the objective of this work was to analyze the influence of cold and hot deformation processing routes on the development of the microstructure, and the consequences on mechanical properties and hydrogen embrittlement. Tensile samples were hydrogenated through gaseous charging and compared to non-hydrogenated samples. Characterization was performed via scanning and transmission electron microscopies, as well as electron backscattered diffraction. The processing was effective to promote significant variations in average grain size and length fraction of special Σ3 n boundaries, as well as reduction of average (Nb, Ti)C particle size, being these changes more intense for the cold-rolled route. For the mechanical properties, on one side, the cold-rolled route presented the highest increase in ductility for non-hydrogenated samples, while, on the other side, had the highest degree of embrittlement under hydrogen. This dual behavior was attributed to the interaction of hydrogen with the (Nb, Ti)C particles and stringers and its ensuing influence on the fracture processes. Graphical abstract: Image 1 Highlights: Σ3 n boundaries and (Nb, Ti)C size and distribution were affected by processing. Processing routes increased the ductility of the non-hydrogenated samples. The loss of ductility due to H was more intense for the cold rolled sample. (Nb, Ti)C act as point of strain localization and ease crack propagation under H.